New species of proparasitylenchus Wachek (Tylenchida, allantonematidae) parasitizing harmonia Axyridis pallas, 1773 (Coleoptera, coccinellidae) in argentina - Camino, Nora (2023)
A new species Proparasitylenchus inalienatus sp. n. is described and illustrated, a parasite of the coccinelid Harmonia axyridis Pallas, 1773 in a locality near Gran La Plata, Colonia Urquiza, Argentina. Of the 13 species described, this species,  it  is characterized by having a cephalic end projecting, faint stylet in its normal place, vulva posterior, tail appendage conoid, with bifurcated tip in both sexes, male with two spicules and a tiny gubernaculum, and leptoderan bursa. We obtained the 18S rDNA partial sequence.